Sistema de gerenciamento de veículos apreendidos para a polícia civil do Estado do Pará - SILVA, Hans William dos Santos (2019)
According to the National Traffic Authority in Brazil (DENATRAN), the state of Pará had an estimated number of 1,908,543 motorized vehicles in November 2017, occupying the first position in the Brazilian northern region. From this number, it is distinguished by 569,057 automobiles and 805,405 motorcycles. On 2016, the state traffic authority published an estimate that the number of motorized vehicles should triplicate by 2020. As a consequence of the increasing number of new motorized vehicles moving by the streets and roads, a negative aspect should be considered: the large incidence of theft and robbery of vehicles in the state. The State Government of Pará playing its constitutional role of public safety and security is responsible to prevent and combat those practices through the Civil Police. In turn, the Civil Police established the Vehicle Theft and Burglary Repression Precinct DRPV, in Portuguese) as the main responsible for this context. Therefore, this work describes the development of web software system to optimize the register and storage of automotive vehicles and parts recovered in actions carried out by the DRFV. This text describes the conclusion of a projected started in 2015 during the undergraduate course on Information Systems in the Federal University of Pará.